At Home in the Academic Library? A Study of Student Feelings of "Homeness". Issue 1 (2nd January 2021) - Mehta, Priya; Cox, Andrew
Abstract: A recent focus in academic library design is as a third place: a home from home. Research has yet to interrogate what it means to be "at home, , and if academic libraries are treated like, and feel like home to students. Seamon's model provides a framework for understanding the qualities associated with homeness, across the five dimensions of rootedness, appropriation, regeneration, at-easeness, and warmth. Using this framework observations were made in two libraries using categories relating to "homeness." It was found that students do act and feel at home in the library. Newer library designs did not facilitate homeness more than older designs. It is concluded that new library designs have the opportunity to make students feel at home by offering flexible spaces to make their own, places to retreat from their desk, and basic amenities.